The analysis of implementation in public relations to establishment the effort of the brand image coworking (a study at coworking space ETOS of Yogyakarta) - Musdalifa, Musdalifa; Fajri, Choirul (Universitas Ahmad Dahlan, 2021)
ETOS co working space, one of the workspaces located in Yogyakarta that carries a simple concept, but is still in demand by the public. Manyhave emerged co-working spaces with attractive concepts and are in demand by many people. ETOS still carries the concept of